2016
DOI: 10.1063/1.4942655
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of surface states of α-Fe2O3(0001) surface by deposition of Ga2O3 overlayers: A density functional theory study

Abstract: There is a big debate in the community regarding the role of surface states of hematite in the photoelectrochemical water splitting. Experimental studies on non-catalytic overlayers passivating the hematite surface states claim a favorable reduction in the overpotential for the water splitting reaction. As a first step towards understanding the effect of these overlayers, we have studied the system Ga2O3 overlayers on hematite (0001) surfaces using first principles computations in the PBE+U framework. Our comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
3
26
1
Order By: Relevance
“…A thick catalyst layer may even counteract photoelectrochemical activity by blocking light absorption or by inhibiting charge transport and ion diffusion from the electrolyte . Moreover, an improvement in the photoelectrochemical (PEC) performance was also observed for noncatalytic overlayers, such as Al 2 O 3 and Ga 2 O 3 , which either passivate surface states, as in the case of Ga 2 O 3 , or change the energetic levels favorably, as in the case of Al 2 O 3 …”
Section: Introductionmentioning
confidence: 80%
“…A thick catalyst layer may even counteract photoelectrochemical activity by blocking light absorption or by inhibiting charge transport and ion diffusion from the electrolyte . Moreover, an improvement in the photoelectrochemical (PEC) performance was also observed for noncatalytic overlayers, such as Al 2 O 3 and Ga 2 O 3 , which either passivate surface states, as in the case of Ga 2 O 3 , or change the energetic levels favorably, as in the case of Al 2 O 3 …”
Section: Introductionmentioning
confidence: 80%
“…In order to avoid being influenced by morphology change or doping effect, Na The enhanced performance could be attributed to the surface catalysis or passivation of the surface state. Normally, the surface decoration of electro-catalysts (e.g., IrO x , Co-Pi [56,57], CoO x ) or deposition with passivation layers (e.g., Al 2 O 3 [47], Ga 2 O 3 [46], SiO x [48]) often highly enhance the PEC performances of Fe 2 O 3 . It has been found that the former played a role mainly through promoting the hole transfer in the interface [57,58], while the latter could decrease the recombination center in the interface works through passivating the surface trap states [47].…”
Section: B Na 2 Moo 4 Ex Situ Mediated Hematite Photoanodesmentioning
confidence: 99%
“…Besides, some undesirable surface states, mainly Fe 3+ /Fe 2+ redox couples and dangling bonds [41,42], exist on the surface of α-Fe 2 O 3 crystallites [43−45], which will act as recombination centers, trapping holes or electrons. Several types of passivation layers, including Ga 2 O 3 [46], Al 2 O 3 [47], SiO x [48] ultrathin layers, have been applied on the surface of Fe 2 O 3 to enhance PEC performance by reducing the charges trapped in the interface between hematite and electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been employed in order to modify hematite among which the following stand: (i) the development of nanostructured architectures, (ii) the improvement of conductivity and promotion of charge transfer ability by metal ion doping, (iii) the reduction of the recombination rate through the employment of passivating layers and (iv) the improvement of the water oxidation kinetics using cocatalysts [10,[29][30][31][32][33]. Surface modification of semiconductor photoelectrodes with passivating overlayers has recently attracted attention as an effective strategy to avoid trapping and hinder surface recombination.…”
Section: Introductionmentioning
confidence: 99%